PENGARUH TINGKAT PDRB, UPAH TENAGA KERJA, DAN POLITICAL RISK TERHADAP FDI DI PROVINSI BALI - Moa Kopa, Maria Carolina; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
This study aims to analyze the simultaneous and partial effect of the level of GRDP, labor wages, and political risk on Foreign Direct Investment (FDI) in Bali Province. The data used is secondary data with panel data analysis to analyze 9 districts/cities in Bali Province in the 2010-2019 period. The analysis technique used is the random effect model (REM) to analyze multiple linear regression, using the classical assumption test, as well as the beta regression coefficient test simultaneously and partially. The results of this study indicate that the GRDP level variable has a positive and significant effect on the level of Foreign Direct Investment (FDI). Meanwhile, labor wages and political risk variables have a negative and significant effect on the level of Foreign Direct Investment (FDI). Based on the results of the study, it is suggested to the Government to optimize the potential of each region in order to overcome the gaps between regions. In addition, the government needs to evaluate and tighten crime regulations so that the crime rate can be reduced to a minimum.